Facing a Green Economy Era: The Role of Madrasah Ibtidaiyah - Efi Tri Astuti; Ratnaningsih Ratnaningsih; Tyas Ayu Setiawati; Septian Kurnia Sari (Yayasan Letiges Konsultan Sosial, 2024)
The research aims to determine the role of MIM Kalikuning 2 Pacitan in fostering an entrepreneurial spirit with a green economy concept. This research uses a qualitative approach with a case study methodology. Data collection techniques include interviews, observation, and documentation. Data were analyzed using the Miles and Huberman approach, a type of narrative analysis, namely analyzing data in the form of stories or narratives to understand individual experiences or perspectives in depth. Meanwhile, source triangulation techniques were used from interview results, observation, and documentation to increase validity and credibility. Research findings show that the role of madrasas is to make a positive contribution to raising environmental awareness (attitudes and behaviour), developing sustainable entrepreneurial skills (innovation and creativity), strengthening relationships between subjects, and teaching about social activities (establishing cooperation with stakeholders), and provide opportunities to become pioneers of change. This role includes implementing an environmentally based curriculum, extracurricular activities, developing green school gardens, utilizing environmentally friendly technology, training and workshops, establishing partnerships with local communities, sustainable skills development, monitoring, and evaluation. Future research needs to be carried out to test the program's effectiveness.